2003
DOI: 10.3102/0013189x032006003
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Scale: Moving Beyond Numbers to Deep and Lasting Change

Abstract: The issue of “scale” is a key challenge for school reform, yet it remains undertheorized in the literature. Definitions of scale have traditionally restricted its scope, focusing on the expanding number of schools reached by a reform. Such definitions mask the complex challenges of reaching out broadly while simultaneously cultivating the depth of change necessary to support and sustain consequential change. This article draws on a review of theoretical and empirical literature on scale, relevant research on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
682
0
26

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 704 publications
(770 citation statements)
references
References 42 publications
13
682
0
26
Order By: Relevance
“…Their role is not to simply implement an "external" innovation or reform, but to develop ownership over the innovation and capacity to deepen the underpinning principles themselves (Coburn, 2003). This principle-based approach to learning innovation represents an idea-centered -as opposed to task-and activity-centered-framework of teaching, with tasks and activities evolved in the service of student idea development (Scardamalia & Bereiter, 1991).…”
Section: Working With the Macro-micro Dynamics For Principle-based Inmentioning
confidence: 99%
“…Their role is not to simply implement an "external" innovation or reform, but to develop ownership over the innovation and capacity to deepen the underpinning principles themselves (Coburn, 2003). This principle-based approach to learning innovation represents an idea-centered -as opposed to task-and activity-centered-framework of teaching, with tasks and activities evolved in the service of student idea development (Scardamalia & Bereiter, 1991).…”
Section: Working With the Macro-micro Dynamics For Principle-based Inmentioning
confidence: 99%
“…Bakah et al (2012b) went back to the study sites after the formal termination of the teacher design teams intervention and found that the concept of teacher design teams had sustained and expanded to other departments and for other curriculum-related problems involving other teachers. The study of Bakah et al (2012b) was framed on theoretical notions provided by theories of change as stated by Coburn (2003). Coburn (2003) describes scaling of innovations as the result of a set of four interrelated dimensions: spread, depth, sustainability and shift in ownership.…”
Section: Agencymentioning
confidence: 99%
“…The study of Bakah et al (2012b) was framed on theoretical notions provided by theories of change as stated by Coburn (2003). Coburn (2003) describes scaling of innovations as the result of a set of four interrelated dimensions: spread, depth, sustainability and shift in ownership.…”
Section: Agencymentioning
confidence: 99%
“…Based on the organizational change literature (Hendry, 1996;Schein, 1996;Stace, 1996) and research on school reform (Cobb et al, 2003;Coburn, 2003;Joyce, 2004), institutionalization of the intervention within the structures and cultures of schools will greatly strengthen the potential for assessment for learning to lead to improved student achievement on a wide scale. But until institutionalization occurs, a bootstrapping problem must be addressed.…”
Section: Assessment For Learning?mentioning
confidence: 99%